Evaluación del bienestar animal entre equinos deportivos en estabulación y equinos de trabajo en pastoreo - Benalcázar Calahorrano, Johanna Lizeth (2023)
The objective of this study was to evaluate the levels of well-being and the problems that occur in three populations of horses that have differences in their management and environmental conditions. They were distributed into three groups and protocols adapted to each of the populations were used. The AWIN (animal welfare international) protocol was used for horses that are in stable conditions; and for the group in pasture conditions, data previously obtained by another study was used, in which a protocol designed specifically for this population was used, since no previously established protocols were found that adapt to the conditions of these horses. The main results obtained were: Pululahua tourist horse horses with a 53.56% probability of well-being; Surveillance horses of the Mounted Police of zone 1 (Ibarra) have a probability of 55.56% of well-being; Equines for equestrian sports in the high sports performance club have a 56% probability of well-being. No group of the three populations of horses studied has a higher percentage of well-being than another, the results are compensatory.